Economic evaluation of postoperative hypofractionated radiation therapy in patients with breast cancer - G. V. Afonin; Yu. A. Ragulin; M. V. Avxentyeva; I. A. Gulidov; S. A. Ivanov; A. D. Kaprin (IRBIS LLC, 2018)
Breast cancer remains the most common malignant neoplasm in women. According to the current standards, radiation therapy is one of the most important components of the multi-disciplinary treatment. The efficacy of the postoperative radiotherapy in both the traditional fractionation regimen and in the hypofractionation mode is not questioned. Contrary to the conventional fractionation, hypofractionation implies an increase in the daily dose and a reduction in the total treatment time. This approach helps reduce the treatment costs in patients with breast cancer while maintaining a high treatment efficacy and quality of life.The aim of the study was to analyze the economic efficiency of the dose hypofractionation as compared to the traditional mode of dose fractionation during postoperative radiation therapy in patients with breast cancer.Materials and methods. The study included 220 patients with breast cancer who received a combined treatment. Of these, 120 patients (study group) received hypofractionated radiotherapy (40.5 Gy in 15 fractions) whereas 100 patients of the control group were treated by the conventional therapy of 50 Gy in 25 fractions. Patients of the both groups were comparable by stages of the disease, systemic treatment, age and molecular type of tumor. The cost of treatment was calculated from the price list of this research center.Results. The present economic analysis showed that the method of hypofractionation was more (30% on average) cost-efficient than the conventional regimen while both modalities produced similar rates of total and relapse-free survival. We were then able to identify the main items in the list of medical services that contributed to the estimated difference in the treatment costs. Reducing the number of examinations and the treatment duration help reduce the expenditure of this medical organization.Сonclusion. Hypofractionation of postoperative radiotherapy in patients with breast cancer allows one to reduce the treatment costs as compared to the conventional fractionation regimen. The funds saved by optimizing the costs of postoperative radiation can be directed to the development of additional means of cancer treatment.